2001
DOI: 10.1007/pl00011337
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Colour Fundus Imaging Using Scanning Laser Ophthalmoscopy

Abstract: The objective of this study was to examine the properties of two laser lines 514 nm and 532 nm when used to image the retina with a scanning laser ophthalmoscope (SLO), and to compare the images taken with a simultaneous multiple wavelength SLO, to those taken with a fundus camera. From this we concluded that the 514 nm line is the preferred line for visualising the nerve fibre layer whereas the 532 nm line is preferred for visualising retinal vessels. Based on these results the 532 nm laser light source was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Structural features of the retinal microcirculation can be examined using analogue or digital fundus photography, or more recently by scanning laser ophthalmoscopy. 22 The relative simplicity of retinal photography means that it can be employed in large-scale epidemiological studies. For example, the Atherosclerosis Risk in Communities Study has shown associations between retinal microcirculatory abnormalities, such as arteriolar narrowing, and the risk of incident stroke.…”
Section: Intravital Microscopymentioning
confidence: 99%
“…Structural features of the retinal microcirculation can be examined using analogue or digital fundus photography, or more recently by scanning laser ophthalmoscopy. 22 The relative simplicity of retinal photography means that it can be employed in large-scale epidemiological studies. For example, the Atherosclerosis Risk in Communities Study has shown associations between retinal microcirculatory abnormalities, such as arteriolar narrowing, and the risk of incident stroke.…”
Section: Intravital Microscopymentioning
confidence: 99%
“…Green lasers have attracted a lot of attention for use in numerous promising applications. Armarium [1][2][3][4][5] is one such application, used in prostate surgery to removing prostatic tissue. 1) 532 nm laser light can eliminate prostatic tissue which can highly and selectively absorb the laser and can result in thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of color imaging to the SLO was first demonstrated by Manivannan et al [13] by using red, green, and blue lasers sequentially to acquire red, green, and blue reflectance images of the retina on a single detector. Simultaneous color imaging with three color lasers and three detectors [14,15] and quasi-simultaneous color imaging using pulsed red, green, and blue lasers and a single detector [16,17] were also demonstrated and shown to obtain color fundus images that resembled color fundus photography but with higher contrast. Recently, an SLO employing adaptive optics has demonstrated color imaging using narrowband red, green, and blue filters on a supercontinuum source with each color obtained sequentially [18].…”
Section: Introductionmentioning
confidence: 99%